The crisis of United States of America' withdrawal from the Iranian nuclear agreement (Damascus University Journal for the economic and Political sciences, 2025)
This study sheds light on the reasons that prompted the United States to withdraw from the Iranian nuclear agreement, the impact of this withdrawal on international relations, and the possibility of a possible Iranian response in the absence of a final formula.Iran's decision to resume its nuclear activities came as a response to America's withdrawal from the nuclear agreement, and the promises of European countries to implement their commitments.Several results were reached in this regard, most notably that this withdrawal had a significant impact on the credibility of the United States of America, and the weakening of confidence in it as an international partner in international agreements, in addition to its destabilization of its position, and the exposure of its intentions related to the lack of desire to maintain international peace and security, And its attempt to contain Iran and keep it away from Russia and China is one of the justifications for its return to revive this agreement.
Keywords: The United States Of America; The Islamic Republic Of Iran; The Iranian Nuclear Deal